Development and validation of a simple spectrophotometric method for the determination of methyldopa in both bulk and marketed dosage formulations - Paulo Roberto da Silva Ribeiro; Reginária Morais Duarte (Universidade de São Paulo, 2014)
A simple, precise, sensitive, rapid, specific and economical spectrophotometric method was developed to determine methyldopa (MTD) content in bulk and pharmaceutical dosage formulations. The proposed method was based on the formation of a colored product from the nitrosation reaction of MTD with sodium nitrite in an acid medium. The resultant nitroso derivative species reacts further with sodium hydroxide and is converted it into a more stable compound. This yellow nitrosation product exhibited an absorption maximum at 430 nm. Beer's Law was obeyed in a concentration range of 6.37 to 82.81 μg mL-1 MTD with an excellent coefficient of determination (R2 = 0.9998). No interference was observed from common excipients in formulations. The results showed the method to be simple, accurate and readily applied for the determination of MTD in pure form and in pharmaceutical preparations. The analytical results obtained for these products using the proposed method are in agreement with those of the Brazilian Pharmacopoeia procedure at a 95% confidence level.